2022
DOI: 10.1002/2211-5463.13519
|View full text |Cite
|
Sign up to set email alerts
|

WDHD1 is over‐expressed in nasopharyngeal carcinoma and may control the expression of ITGAV

Abstract: Nasopharyngeal carcinoma (NPC) is a highly metastatic and invasive malignant tumor that originates in the nasopharynx. The DNA‐binding protein WD repeat and HMG‐box DNA‐binding protein 1 (WDHD1) are highly expressed in a variety of tumours, but its expression and mechanism of action in NPC have not been reported to date. To investigate the involvement of WDHD1 in NPC, we first mined databases for the gene expression profile of NPC. Immunohistochemistry (IHC) was performed on 338 cases of NPC and 112 non‐NPC sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…As validated by bioinformatics and cellular experiments, respectively, Chen et al and Liu et al found that WDHD1 was associated with lymph node metastasis in CESC and CHOL [ 63 , 66 ]. Furthermore, several studies have shown that WDHD1 is associated with the regulation of tumor cell stemness, chemoresistance, and cell cycle regulation [ 13 , 16 , 67 ]. Of particular note, Ertay et al proposed that WDHD1 may control stemness of phosphatase and tensin homolog (PTEN)-inactive triple-negative breast cancer (TNBC) cells through its ability to regulate and protein translation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As validated by bioinformatics and cellular experiments, respectively, Chen et al and Liu et al found that WDHD1 was associated with lymph node metastasis in CESC and CHOL [ 63 , 66 ]. Furthermore, several studies have shown that WDHD1 is associated with the regulation of tumor cell stemness, chemoresistance, and cell cycle regulation [ 13 , 16 , 67 ]. Of particular note, Ertay et al proposed that WDHD1 may control stemness of phosphatase and tensin homolog (PTEN)-inactive triple-negative breast cancer (TNBC) cells through its ability to regulate and protein translation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there has been a concerning increase in the age of onset, leading to significant financial burdens for patients' families and society at large [90]. In NPC, WDHD1 expression levels are notably upregulated, suggesting its potential effect on the dynamics of the cell cycle through the regulation of integrin alpha V (ITGAV) expression [78]. Furthermore, bioinformatic analyses have indicated that WDHD1 could serve as a discriminatory biomarker for distinguishing the NPC cohort from the non-cancer control group, holding promise as a novel screening molecule for NPC.…”
Section: Wdhd1 and Nasopharyngeal Carcinomamentioning
confidence: 99%